It may be History, but is it true?: The imperial War Museum Conference. - Nelson, Michael (Historical Journal of Film, Radio & Television, 2005)
The article presents information on the conference on history on television that was held at the Imperial War Museum in London on October 15, 2004. The conference, which was introduced by Christine Whittaker, President of the International Association for Media and History (IAMHIST), was organized by IAMHIST, the Imperial War Museum, and the British Universities Film and Video Council and Society for Screen Based Learning. The conference had several sessions. One of the sessions was based on the topic "The Face of History: The Historian on Television." According to one of the speakers Stephen Badsey, a military historian, one thing about the involvement with television history, and something which puts many historians firmly off the idea, is that rather than being seen as professionals or experts, for television people historians are slightly superfluous to their needs. They would not dream of making gardening programmes without gardeners, or science programmes without scientists, but they are quite prepared to make history programmes without historians.